Mitigation of tip vortex cavitation by means of air injection on a Kaplan turbine scale model - Rivetti, Arturo (2014)
Kaplan turbines operating at full-load conditions may undergo excessive vibration, noise and cavitation. In such cases, damage by erosion associated to tip vortex cavitation can be observed at the discharge ring. This phenomenon involves design features such as (1) overhang of guide vanes; (2) blade profile; (3) gap increasing size with blade opening; (4) suction head; (5) operation point; and (6) discharge ring stiffness, among others. Tip vortex cavitation may cause erosion at the discharge ring and draft tube inlet following a wavy pattern, in which the number of vanes can be clearly identified. Injection of pressurized air above the runner blade centerline was tested as a mean to mitigate discharge ring cavitation damage on a scale model. Air entrance was observed by means of a high-speed camera in order to track the air trajectory toward its mergence with the tip vortex cavitation core. Post-processing of acceleration signals shows that the level of vibration and the RSI frequency amplitude decrease proportionally with air flow rate injected. These findings reveal the potential mitigating effect of air injection in preventing cavitation damage and will be useful in further tests to be performed on prototype, aiming at determining the optimum air flow rate, size and distribution of the injectors.